Transannular interactions in mixed superphanes with one thiophene and one cpco-stabilized cyclobutadiene ring: syntheses, structures, and electrochemistry - Stäb, Silke; Gleiter, Rolf; Rominger, Frank; Bleiholder, Christian (Organometallics, 2007)
Superphanes consisting of one thiophene ring and various substituted RCo-stabilized cyclobutadiene (CBD) rings (R = Cp, C5H4(CH3), C5(CH3)5, C5H4(Si(CH3)3), C5H4(COCH3), 8−12) and one superphane with one thiophene ring and one CpCo-stabilized cyclopentadienone ring (13) were synthesized. The starting point was a tricyclic diyne with a central thiophene ring and two condensed 4-cyclodecynes, 19. Heating of 19 with RCo(COD) yielded 8−12, whereas the heating of 19 with CpCo(CO)2 gave 13. X-ray structural investigation of 8−13 afforded the geometrical parameters in the solid state. Cyclic voltammetry showed a strong interaction between the thiophene ring and the CpCo-stabilized cyclobutadiene part. This interaction was substantiated by comparison between the CV data of 8−12 and model systems containing only the CpCo(CBD) part.